Labor remuneration for higher education teachers: economic and legal issues of incentive and compensation payments - P. V. Zobov; M. V. Erkhova (Вестник университета)
The article considers the regulatory mechanism of remuneration of teachers, the specifics of the economic component of remuneration in higher educational institutions of the Russian Federation. The fundamental differences between economics and legal regulation of incentive payments to teachers of higher education have been investigated, aspects of compensation payments have been analysed. A number of problems of an economic, regulatory and law enforcement nature have been identified, which can reduce the motivation of the pedagogical community and negatively affect the quality of training of graduates of higher school. For each problem area, proposals have been developed to improve the provision of incentive and compensation payments in higher education institutions. The proposals are designed to increase the demand for pedagogical work and the competitiveness of domestic universities and enterprises.